PENGARUH BRAND IMAGE DAN SERVICE QUALITY TERHADAP KEPERCAYAAN GUNA MELENGKAPI LOYALITAS PELANGGAN PADA PRODUK KOSMETIK MS GLOW PADA MAHASISWA MANAJEMEN UNIVERSITAS MUHAMMADIYAH BENGKULU - Oktaria, Tesa Dwi; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
Based on the results of research that has been conducted on the effect of Brand Image (X1), and Service Quality (X2), on trust (Y) to increase Consumer Loyalty (Y1) in using MS Glow Products, it can be concluded as follows: Brand Image (X1) has an effect on Trust (Y) in using the product. This can be seen from the results of research conducted with a path coefficient of 0.591, Services Quality (X2) has an effect on Trust (Y) in using the product. It can be seen from the results of research conducted that is equal to 0.274, Trust (Y) affects Consumer Loyalty (Y1) in using the product. This can be seen from the results of research conducted with a coefficient of 0.383, Brand Image (X1) has an indirect effect on Consumer Loyalty (Z) in using the product. This can be seen from the results of research conducted with a coefficient of 0.638 Services Quality (X2) has an indirect effect on Consumer Loyalty (Z) in using the product. This can be seen from the results of research conducted with a coefficient of 0.205, Trust (Y) to Consumer Loyalty (Y1) for MS Glow products among students at the Muhammadiyah University of  Bengkulu. This can be seen from the β efficiency of 0.383 or 38.3% with a significant level of 0.000 <0.050, then H0 is rejected, which means that there is a positive and significant influence between Brand Image on Consumer Loyalty. Keywords: Brand Image and Service Quality, trust, Consumer Loyalty